Profile of Critical Thinking Students of Class X IPA SMA Al Hikmah Banyuwangi on Virus Material - Aristi, Fayzah; Zulfiana, Nanda Harisma; Elfirida, Salsabila; Sya'adah, Wildatus (META: Journal of Science and Technological Education, 2022)
Critical thinking is one of the higher order thinking skills (HOTS) required to make judgements and decisions in order to solve an issue in a thoughtful and sensible manner. The purpose of critical thinking is to develop a profound knowledge that enables one to comprehend the meaning of a concept and discover the significance of an event. The research method used is a qualitative descriptive research type with data obtained objectively describing the level of critical thinking of students in class X IPA SMA Al Hikmah Banyuwangi, the subject of this research is students in class X with a total of 25 odd semester students for the 2022/2023 school year with observations using 7 questions covering 5 aspects of assessment. Making inferences/conclusions received a score of 54.66 in the sufficient category, managing strategy and tactics received a score of 50.66 in the low category, giving further explanation received a score of 46.66 in the low category, giving a simple explanation received a score of 67.33 in the sufficient category, and building basic skills received a score of 76 in the high category. These findings may serve as a resource for instructors looking for new learning innovations that help increase students' critical thinking abilities via a variety of ways, one of which is problem-based learning.